Effect of maternal and infant vitamin D supplementation on vitamin D levels of breastfed infants - Buğrul, Fuat; Devecioğlu, Esra; Ozden, Tülin; Gökçay, Gülbin; Omer, Beyhan (The Turkish Journal of Pediatrics, 2013)
The aim of our study was to investigate the effect of maternal vitamin D3 (400 U/day) supplementation on breastfed infants at 6 months of age. Mothers (n=96) were enrolled within 1 month after birth and assigned to the 400 IU/day regimen or no vitamin D3 supplementation for 6 months. All infants received 400 IU/day of vitamin D3 and were exclusively breastfed until 4 months of age. Of all mothers, 22.2% had vitamin D levels above 20 ng/ml initially. At the end of the study, vitamin D levels of mothers and their infants were similar in both groups. Thirteen percent of the infants in the intervention group and 20.5% in the control group had vitamin D levels below 12 ng/ml. Serum 25-hydroxyvitamin D (25(OH)D) concentrations at 6 months had increased significantly in mothers in the intervention group. Lactating mothers and their children need vitamin D supplementation but further studies are required with higher doses.